Biomimetic Nanovaccines Potentiating Dendritic Cell Internalization via CXCR4‐Mediated Macropinocytosis. Issue 5 (7th December 2022) - Yang, Chao; Zhang, Fan; Chen, Fangman; Chang, Zhimin; Zhao, Yuewu; Shao, Dan; Sun, Wen; Dong, Wen‐fei; Wang, Zheng
Abstract: Although targeted delivery of nanoparticulate vaccines to dendritic cells (DCs) holds tremendous potential, it still faces insufficient internalization and endosome degradation via the receptor‐mediated endocytosis pathway. Inspired by the advantages of CXC‐chemokine receptor type 4 (CXCR4)‐mediated macropinocytosis in the internalization of DCs, a multifunctional vaccine is constructed based on a reactive oxygen species (ROS)‐responsive nanoparticulate core and macropinocytosis‐inducing peptide‐fused cancer membrane shell, allowing the direct cytosolic delivery of cancer membrane‐associated antigen and a stimulator of interferon genes (STING) agonist, cGAMP for highly efficient cancer immunotherapy. The biomimetic nanovaccines show a dramatically enhanced cellular uptake by DCs via CXCR4‐mediated macropinocytosis. Such a direct delivery process promotes cytosolic release of cGAMP in response to ROS, and together promoted DC maturation and T cell priming by activating the STING pathway. Consequently, the biomimetic nanovaccines not only result in a great tumor rejection in prophylactic B16‐F10 melanoma murine model, but also markedly suppress the growth of established melanoma tumors when combined with anti‐PD‐1 checkpoint blockade. This study advances the design of biomimetic nanovaccines and provides a promising strategy for macropinocytosis‐mediated cancer vaccination. Abstract : Inspired by the advantages of macropinocytosis in the internalization of dendritic cells (DCs), a multifunctional nanovaccine is developed, allowing a dramatically enhanced cellular uptake by dendritic cells via CXCR4‐mediated micropinocytosis and subsequently cytosolic release of adjuvants in response to reactive oxygen species for promoting dendritic cells maturation and T cell priming.